Unraveling Disability Participation in Indigenous Peoples - Isnenningtyas Yulianti; Nurrahman Aji Utomo (Journal of Southeast Asian Human Rights, 2019)
Abstract The issue of disability in indigenous peoples is closely related to the issue of full enjoyment in development and inclusive citizenship. Indigenous peoples have the potential to face discrimination and exclusion from every development from every aspect of life. This condition becomes more vulnerable if it occurs in persons with disabilities. The issue of disability in indigenous peoples, still often neglected in its environment and its own group, and even in the system of society and state. Toraja, Bali, and Maros became the representation of the research area. Based on facts and analyzes, disabilities in indigenous peoples face various layers of discrimination and violations of gender and disability status. The characteristics of indigenous peoples determine the treatment of persons with disabilities in their communities. Most noticeable is the lack of friendly service for persons with disabilities in their own societies. Therefore, people with disabilities in indigenous peoples need open opportunities to participate in customary institutions and emancipation beyond the scope of protection and the fulfillment of rights by the government.